Personality Disorders and Mindreading: Specific Impairments in Patients With Borderline Personality Disorder Compared to Other PDs. Issue 8 (August 2015) - Semerari, Antonio; Colle, Livia; Pellecchia, Giovanni; Carcione, Antonino; Conti, Laura; Fiore, Donatella; Moroni, Fabio; Nicolò, Giuseppe; Procacci, Michele; Pedone, Roberto
Abstract : Abstract: The capacity of understanding mental states is a complex function which involves several components. Single components can be selectively impaired in specific clinical populations. It has been suggested that impairments in mindreading are central for borderline personality disorder (BPD). However, empirical findings are inconsistent, and it is debatable whether BPD presents a specific profile of mindreading impairments. The aim of this study is to compare BPD and other PDs in mindreading. Seventy-two patients with BPD and 125 patients with other PD diagnoses were assessed using the Metacognition Assessment Interview. BPD showed difficulties in two mindreading functions, differentiation and integration, even when the severity of psychopathology was controlled. These results suggest a specific mindreading impairment in BPD and a strong relationship between these impairments and the severity of psychopathology.